Rynek nieruchomości i jego uczestnicy a zapotrzebowanie na informację prognostyczną - Bartłomowicz, Tomasz (Real estate market, market's participants and demand for forecast information, 2005)
The article presents demand for special forecast information for various real estate market’s participants. Three tables of suggestions have been proposed: forecasting in local, regional and national area of real estate market. There are also kind and recipients of prognosis discussed in the paper. In author’s opinion presented suggestions can be used as the starting point to further research (forecasting) of real estate market.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (15); 2005; nr 1096, s. 140-147